Study of Fluid Flow Characteristics In A 90° Pipe Bend With Varying Guide Vane Length - Julian, James; Purba, Riki Hendra; Sedeq, Khalees; Wahyuni, Fitri; Junaedi, Thomas (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2024)
The influence of guide vane length and Reynolds number was investigated using computational fluid dynamics methods. By using a structured mesh, it is known that the three mesh variations used have been verified using the Richardson Extrapolation method. The validation process also showed quite good results. From this research, it can be seen from the velocity profile trend, which is close to the experimental results from previous studies. Changing the Reynolds number does not significantly change the velocity profile at the outlet bend. However, it can be seen that changes in the Reynolds number impact the fluid flow pattern produced around the pipe bend. It can be seen clearly, especially when the velocity is negative. Changing the length of the guide vane changes the flow pattern quite significantly. It is known that the shorter the guide vane used, the velocity profile will tend towards the outer core. Furthermore, using a guide vane increases the velocity profile at the position -0.3≤r/R≤ -0.06. Using a guide vane has proven to eliminate negative velocity areas on the inner core side of each variation.